2012 45th Hawaii International Conference on System Sciences 2012
DOI: 10.1109/hicss.2012.226
|View full text |Cite
|
Sign up to set email alerts
|

Do Me a Solid? Information Asymmetry, Liking, and Compliance Gaining Online

Abstract: As the popularity of interactive social media grows, it is increasingly normal for individuals to reveal significant amounts of personal information online. Although this information is intended to support social networks, it can potentially be misused. We hypothesize that access to routine network site profile information can enable individuals to foster feelings of interpersonal attraction in their communication partner, which should increase the likelihood that their partner complies with requests for help.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Digital Transformation (DT) has become a new phenomenon with the rise of new digital technologies such as Internet of Things (IoT), big data, cloud computing, mobile systems and collaboration networks (Zimmermann, Schmidt, Bogner, Jugel, & Möhring, 2018). DT is defined as the use of new digital technologies that enables major business improvements and influences all aspects of customers' life (Reis, Amorim, Melão, & Matos, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Digital Transformation (DT) has become a new phenomenon with the rise of new digital technologies such as Internet of Things (IoT), big data, cloud computing, mobile systems and collaboration networks (Zimmermann, Schmidt, Bogner, Jugel, & Möhring, 2018). DT is defined as the use of new digital technologies that enables major business improvements and influences all aspects of customers' life (Reis, Amorim, Melão, & Matos, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus systematic differences in language content would be observed. Recent research has revealed potential for a variety of explanations pertaining to the link between information asymmetry given that asymmetric information can be leveraged to produce interpersonal attraction (Hancock, Toma, & Fenner, 2008) and compliance (Claes, Hurley, & Stefanone, 2012).…”
mentioning
confidence: 99%